PREVALENCE AND ASSOCIATED FACTORS OF DENTAL CARIES, GINGIVITIS, AND CALCULUS DEPOSITS IN SCHOOL CHILDREN OF SARGODHA DISTRICT, PAKISTAN - Umer, Muhammad Farooq; Farooq, Umer; Shabbir, Arham; Zofeen, Shumaila; Mujtaba, Hasan; Tahir, Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Background: According to a pathfinder survey conducted by World Health Organization, dental caries is the single most common chronic childhood disease in Pakistan. The update information regarding dental health of school children of Sargodha district is required to plan community caries prevention programs and for better understanding of existing situation, and may improve longevity, treatment, and care. Methods: This cross sectional study was conducted in four randomly selected schools of Sargodha district, stratified by gender selected. Two well-trained dentists examined the oral cavities of children for dental caries, gingivitis, and calculus deposits. The sample consisted of children aged between 3-12 years. Results: The overall prevalence rate of gingivitis, calculus, and dental caries was found as 14.5%, 14.3%, and 45.9% respectively. A significant association was found between DMFT score (p<0.001), gingivitis (p<0.01), and calculus (p<0.05) with the increase in age of children. More children living in urban area were detected with gingivitis (p<0.01), calculus (p<0.01), and dental caries than children residing in rural areas. Incidence of gingivitis (p<0.05), calculus, and dental caries in primary (p<0.001) and permanent teeth were found higher in those children who were not brushing their teeth. Experience of dental caries in primary teeth was found higher (p<0.01) in children who brushed occasionally. Study also showed that none of the children ever visited dentist for treatment. Conclusions: The results emphasize the need for initiation of awareness programs to achieve 0 DMFT/df scores.